Lexicologie als universitaire vakopleiding - Martin, W. (Lexikos, 1994)
Lexicology as University Vocational TrainingThis article consists of two parts. Part one (paragraphs 1-3) deals with the notion 'lexicon', part two (paragraphs 4-7) introduces and presents the study programme 'Lexicology' such as it is conceived at the Free University of Amsterdam. The lexicon as object of study is taken up as 'an organized lexical knowledge bank that language users have at their disposal and which enables them to produce and understand language (at lexical level)'. The main concern of lexicology therefore is the organization and structure of such a bank. The role played by it in both language production and language understanding is illustrated. In the part dealing with the study programme 'Lexicology' itself most attention is paid to the final attainment levels. A distinction is made between common-general and more specific ones. As to the common-general ones the notion 'lexical knowledge' plays a central role. The various ways of its definition, representation, derivation, exploitation and application are all to be considered. As to the more specific attainment levels a differentiation is made according to 'study-paths', viz. --- lexicography --- terminology / terminography --- and computational lexicology For all three of them, a short characterization in terms of motivation, aim, final attainment levels and job opportunities is given. Finally a survey is given of the actual study programme (including the one for the European Lexicography Diploma) so to make clear the relationship between theory and practice and to clarify the notion 'professional training at university level'.